iPhone User Consumer Irrational Behavior - Hayatd, Alphatihatul; Dwi Haryanto, Niko; Mareta, Andini (JAMBIS : Jurnal Administrasi Bisnis, 2024)
The iPhone seems to have its own charm compared to other brands, especially for themillennial generation, whose decisions are mostly based on their immediate environment. Thisstudy aims to explain the existence of irrational phenomena that occur in iPhone users. Thisresearch use desciptive qualitative approach. The data obtained comes from literature studiesand also observations. The results of the study explain that consumers who use Iphone haveirrational behavior, for example, there are Iphone rental services, renting screenshot features,videos and reposting stories on Instagram, doing everything possible to be able to buy thelatest iPhone series products with excessive credit, taking pictures on the reflection of theglass on purpose displays the iPhone logo. Conclusion on this research. The image andbranding attached to the Iphone is what causes phenomena to occur. Factors of irrationalbehavior among Iphone users feel pressured and expelled from their community when theycannot follow their surroundings.